حقوق المملوكين فى الأحكام، ومكارم الأخلاق: دراسة تاريخية - حبيب، ثامر عبد على (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2019)
تقع الدراسة في ثلاث مباحث، يتضمن المبحث الأول: لمحة عنهم في الأمم الأخرى والعرب في الجاهلية، مصادر المملوكين، نماذج من العتق في الجاهلية. والمبحث الثاني تضمن: حقوقهم في الأحكام (العتق والحدود)، حرمة دمائهم، أعراضهم، منزلتهم، جمع شملهم، معاملتهم (إكرامهم، مشاركتهم الطعام، لباسهم، التجاوز عنهم، تأديبهم برفق، عدم تكليفهم فوق طاقتهم، زواجهم. وخصص المبحث الثالث، للعتق في مكارم الأخلاق، عتقاء النبي (صلى الله عليه وسلم)، آل البيت (عليهم السلام) والصحابة (رضي الله عنهم) وعامة المسلمين، ثم عتق الولاة، ونختم عتقهم لأخلاقهم.
The study is divided into three sections the first topic includes the study of other nations and the arabs in the Jaahiliyyah the sources of the Mamluks motives and reasons are examples of ignorance in the Jaahiliyyah the second topic includes their rights in the provisions (punishments) the sanctity of their blood, their symptoms, their status, their reunification, their treatment, their participation, their food, their clothing pardons, Third topic their gentle discipline not being overstretched, their marriage the salvation of the prophet the House the companions and the general Muslims and then the rulers are exhausted and we conclude their freedom of ethics.
Keywords: العتق -- الحدود -- الأخلاق الإسلامية -- الشريعة الإسلامية